Pengaruh Financial Literacy, Lifestyle, Konformitas, Money Attitude, dan E-Money terhadap Perilaku Konsumtif Generasi Z Penggemar Korean Wave di Kota Surabaya - Marisyah Dwi Ambarsari; Nadia Asandimitra (Jurnal Ilmu Manajemen, 2023)
This research analyses the relationship between financial literacy, lifestyle, conformity, money attitude, and e-Money on consumptive behaviour. The object of this research is Generation Z K-pop fans residing in Surabaya, and the research utilizes purposive sampling and snowball sampling techniques in collecting data. It was obtained from around 209 Generation Z teenagers who are K-pop fans in Surabaya due to the distributed online questionnaire. This research adopts Structural Equation Modeling (SEM) analysis technique on AMOS software version 24 in producing the conclusive causality. The results of this study indicate that lifestyle, conformity, money attitude, and e-Money significantly influence consumptive behaviour. While financial literacy is not significantly influenced by consumptive behaviour because the conditions of each individual will vary based on factors such as needs, environment, and culture. This research intends to aid various parties in realizing the importance of self-control in managing money and adapting to the social environment. Thus, the subjects will not be easily affected by the ever-changing lifestyle to make rational financial decisions, especially for the Surabayan Generation Z, who are K-pop fans.